2012
DOI: 10.1111/j.1472-765x.2012.03253.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of CTX prophage in Vibrio cholerae

Abstract: Aims:  The objective of this study was to investigate the molecular diversity of CTX genetic element within toxigenic Vibrio cholerae genomes and to determine the genetic diversity of V. cholerae population collected in a 6‐year period (2004–2009) in Iran. Methods and Results:  The results of mismatch amplification mutation assay (MAMA)‐PCR and sequencing showed cytosine nucleotide in positions 203 and 115 in all 50 El Tor V. cholerae strains, which is the same as classical ctxB sequence. One strain yielded am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…7 Results of PFGE analysis in this study revealed the cholera isolates were in different clusters. Ogawa serotype was a main type of the outbreak of 2011.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…7 Results of PFGE analysis in this study revealed the cholera isolates were in different clusters. Ogawa serotype was a main type of the outbreak of 2011.…”
Section: Discussionmentioning
confidence: 88%
“…This serotype was distributed through the country with 6 different patterns, while a few Inaba strains were only isolated with differentiated patterns from Ogawa serotype. 7 In the present study, the diversity of cholera strains in 2013 outbreak was studied and the results were compared with the homology of detected Inaba strains in 2011. We concluded the previous native Inaba strain could not have a role in 2013 outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations